OLAHRAGA DAN KESEHATAN MENTAL DARI PERSPEKTIF SOSIOLOGI OLAHRAGA SEBUAH KAJIAN LITERATUR - Zai, Niada; Ayu Tamara; Evalince Agnes Amo; Palmarum Glenovian Hutahaean; Pandapotan Bintang; S. Aira Julia Br Ginting; Nurkadri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the relationship between sports participation and mental health from the perspective of sports sociology. Employing a Systematic Literature Review (SLR) method, this study examines various recent scholarly literature discussing the social dynamics of sports and their impact on individuals’ psychological well-being. The findings reveal that sports participation provides significant positive contributions to mental health through the formation of social capital, increased group support, strengthened sense of belonging, and the development of character traits such as discipline, resilience, and cooperation. On the other hand, the study also identifies potential negative impacts, including excessive competitive pressure, discrimination based on gender and social class, and supporter violence that can exacerbate mental health conditions. From the sports sociology perspective, sports is viewed not merely as a physical activity, but as a social practice influenced by and influencing societal structures, norms, and interactions. Therefore, integrating a sociological approach into physical education and public sports policy is essential to maximize the benefits of sports while minimizing its risks to the mental health of the younger generation in Indonesia